Diagnostic value of metagenomic next generation sequencing of bronchoalveolar lavage fluid in immunocompromised patients with pneumonia - Xin, Liu; Jiao, Xiaodan; Gong, Xiaowei; Yu, Jing; Zhao, Jing; Lv, Jing; Feng, Qixuan; Yuan, YaDong; Pan, Wensen (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundMetagenomic next-generation sequencing (mNGS) enables simultaneous sequencing of DNA fragments for comprehensive pathogen identification. Pneumonia in immunocompromised patients—characterized by atypical clinical manifestations and rapid progression—poses diagnostic challenges. Conventional microbiological testing (CMT), which relies on pathogen culture and serological assays, is limited by prolonged turnaround times and suboptimal detection rates. This study was performed to evaluate the clinical utility of mNGS through comparative analysis with CMT in detecting pathogens among immunocompromised patients with pneumonia.MethodsWe conducted a retrospective cohort study of 146 immunocompromised patients with suspected pneumonia. The mNGS and CMT results were systematically analyzed. Pathogen detection rates and microbial spectrum concordance were visualized using pie and bar charts. Diagnostic performance was compared using McNemar’s test and Kappa (κ) statistics for inter-method agreement. The sensitivity, specificity, accuracy, and area under the curve were calculated for pathogen-specific evaluations.ResultsmNGS demonstrated superior detection efficacy, identifying pathogens in 98 cases versus 50 by CMT, with 48 overlapping positives. The microbial spectrum showed substantial differences: mNGS detected 73 bacterial, 46 fungal, and 45 viral pathogens, whereas CMT identified 38 bacterial, 27 fungal, and 21 viral agents. mNGS outperformed CMT across all infection types, including single-pathogen infections (bacterial, fungal, or viral only) and mixed infections (bacterial + fungal, bacterial + viral, fungal + viral, or bacterial + fungal + viral). Bacterial and fungal detections showed low inter-method concordance, while viral detection exhibited moderate agreement (κ = 0.510, p < 0.001). Notably, mNGS achieved significantly higher detection rates for Enterococcus faecalis and Pneumocystis jirovecii in intensive care unit (ICU)-admitted patients with severe pneumonia (p < 0.05). Clinical outcomes improved in 45 patients following mNGS-guided therapeutic adjustments.ConclusionsmNGS and CMT demonstrate complementary strengths in bacterial and fungal detection in immunocompromised patients with pneumonia. mNGS provides enhanced diagnostic accuracy for key pathogens such as E. faecalis and P. jirovecii, particularly in severe and ICU-admitted cases. As a high-throughput diagnostic tool, mNGS may improve pathogen detection and clinical management in immunocompromised populations.